Adapting public policies and public administration to the needs of physically challenged people - Rammata, Maria (International Conference on Business and Economics - Hellenic Open University, 2025)
It is imperative that individuals with disabilities and other vulnerable social groups are afforded special consideration as citizens and especially as users of public administrations when they try to settle their cases. However, it is not always confirmed that institutions, administrative procedures and overall public policies are adapted to the needs of vulnerable people. Neither is it given that civil servants are recipients of an adequate training that enables them to deal with the various disabilities and specifications of each case. This study demonstrates that the public sector must evolve to more effectively cater to the needs of persons with disabilities and be alerted of their future requirements and specific living conditions. This necessity is attributable to a number of factors, including the prevailing systems, the policy-making process, the administrative burdens and the human resources available, which are not sufficiently qualified to support persons with disabilities and other vulnerable groups. General decisions and directions have been established to clarify the necessity for immediate modifications to be implemented by the public sector in order to embrace persons with disabilities in political, economic and social life. Proposals are to be presented regarding the requisite reforms to be introduced in the administrative corpus of public administrations. These reforms will pertain to the design of public policies and services, the impact of communication policy, the physical accessibility and the environment within the administrations, the assessment method of disability (medical model) and finally, the disability awareness for the personnel in public administration. JEL Classifications: D1, I3, I31, K0 Keywords: Discrimination, disability, accessible public services, stigma, isolation, disability awareness, allowance, immigrants, equality, inclusiveness